Chinese Ways of Seeing and Open-Air Painting (Book collections on Project MUSE., 2020)
"Focuses on the rise of open-air painting in modern China beginning in the late 1910s, when the New Culture Movement prompted painters to embrace direct observation, linear perspective, and a conception of vision based on Cartesian optics, through the early 1960s. The new landscape practice brought with it unprecedented emphasis on perception and redefined artistic expertise"--